Eksplorasi Bambu Betung Untuk Pembuatan Lampu Hias - Edi Eskak (Ornamen, 2012)
Bamboo betung (dendrocalamus asper) is a big and tall bamboo species in Indonesia which come in potentially abundant. This bamboo has its advantages as a thick reed, tubular hollow tube in natural form which is strong enough to meet the technical requirements to be tested  as a wood substitute materials in the manufacture of products interior accessories with technical krawangan (hole). Despites its superior characteristics mentioned above, carved bamboo betung also has the disadvantage that is difficult when it is carving because of its straight and easy fiber to split. This is a question that will be examined to find a solution from this research. In the implementation of pilot activities to the manufacture of interior accessories on bamboo betung krawangan carving techniques, the process consists of the initial formation, krawangan making, carving and finishing. It has been equipped also with profound observations about  the bamboo betung, techno economic calculation. From the results showed that the hole techniques (krawangan)  with four times in drilling then its forwarded with hand saws jigsaw obtained an average speed (4 x 5.1) + 20 = 40.4 seconds for the hole size 3-4 cm, thick 1.5 cm straight curved shape variation, in bamboos half-wet conditions (magel). This means 5 times faster than the manual sculpting (209.1 seconds), and the results are neater and cleaner. The  best conditions for making krawangan is half wet conditions (magel) and the water content of bamboo is 30-60%. Keywords: bamboo betung, krawangan carving, decorative lights.